Enantiomorphic double-polymerized chiral polymer composite template for highly efficient energy-saving green window. (18th June 2020) - Lin, Jia-De; Wu, Meng-Huan; Jiang, Shun-An; Zhang, Yan-Song; Chen, Hung-Lin; Mo, Ting-Shan; Lee, Chia-Rong
Abstract: An infrared (IR) reflector that has ultra-wide reflection band and high reflectance was successfully fabricated based on an enantiomorphic chiral polymer composite template-made method involving UV-curing, washing-out, stacking, and refilling. In this study, an IR reflector reflecting >80% of incoming solar IR light from 800 nm to 1500 nm and retaining acceptable transmittance in the visible region is demonstrated. This undertaking is achieved by stacking two enantiomorphic double-polymerized chiral polymer templates with large longitudinal pitch gradients as a composite template cell designed for the near-IR region. Heat insulation test reveals that the temperature can be effectively lowered by 2 °C–3 °C by using the IR reflector, thereby indicating that a considerable amount of incident heat could be isolated and a significant amount of energy could be saved by cooling. The sample has potential in green and military applications, such as energy-saving green windows and anti-IR devices. Graphical abstract: Image 1 Highlights: Liquid crystal/polymer composites reflecting near-infrared light of solar spectrum. Green building materials work for both left- and right-handed circular polarizations. Semi-transparent and hazy film effectively lowers indoor temperature. High flexibility for more add-on functions such as anti-UV irradiation.